Issues to Improve Auditor Quality Control - Kushmatov Otakhon Kurbanalievich (International Journal on Economics, Finance and Sustainable Development, 2022)
In this article discussed the form, criteria and procedures of quality control of the auditor's work during the audit and given recommendations for improvement.